Dinosaur hunt (Kuala Lumpur : Vscape Enterprise [distributor], 2002)
Of all the creatures that ever walked the earth, none captures the human imagination like the dinasour. To some of us they are almost mythical, a modern-day version of the dragons and monsters of fairy tales. But to scientists they hold a different fascination, offering important clues to the mystery of the evolution of life.
Keywords: Dinosaurs in motion pictures